Nonsurgical Intervention in a Preeclamptic Patient with Spontaneous Spinal Epidural Hematoma - Michelle Nguyen; Maria Raquel Kronen; Alex Nhan; Antonio Liu (Case Reports in Obstetrics and Gynecology)
Background. Spontaneous epidural hematoma (SEH) is a rare finding in pregnancy, especially since most pregnant women do not have risk factors for developing SEH. The presence of epidural anesthesia can delay the diagnosis of SEH in pregnant patients. Immediate surgical decompression is the current standard of care for treating SEH. Case Presentation. We present the case of a 37-year-old pregnant woman with preeclampsia with severe features who developed neurological deficits that were initially attributed to her epidural anesthesia. She was eventually found to have SEH with spinal stenosis at T5-T6 on MRI. Oral antihypertensives were used to keep the patient’s blood pressures within normal limits, and she subsequently had complete resolution of her neurological symptoms and her SEH on imaging. Conclusion. Preeclampsia may contribute to the development of SEH in pregnancy, and strict blood pressure control may potentially provide a safe and effective alternative to neurosurgery for these patients.